If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -6(x + -1) = 7(3 + x) Reorder the terms: x + -6(-1 + x) = 7(3 + x) x + (-1 * -6 + x * -6) = 7(3 + x) x + (6 + -6x) = 7(3 + x) Reorder the terms: 6 + x + -6x = 7(3 + x) Combine like terms: x + -6x = -5x 6 + -5x = 7(3 + x) 6 + -5x = (3 * 7 + x * 7) 6 + -5x = (21 + 7x) Solving 6 + -5x = 21 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + -5x + -7x = 21 + 7x + -7x Combine like terms: -5x + -7x = -12x 6 + -12x = 21 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + -12x = 21 + 0 6 + -12x = 21 Add '-6' to each side of the equation. 6 + -6 + -12x = 21 + -6 Combine like terms: 6 + -6 = 0 0 + -12x = 21 + -6 -12x = 21 + -6 Combine like terms: 21 + -6 = 15 -12x = 15 Divide each side by '-12'. x = -1.25 Simplifying x = -1.25
| 0.6(15d+20)-6(18d-12)=38 | | -3.5+4.6+1.6x+7=x-3.9 | | -12=z-3 | | -2x+2+6=-3 | | 5.3=-6+x | | -2(-c-20)=-2c-20 | | 6(7x-2)=72 | | 56=8-8(1+7v) | | 6m+6=30 | | 1.5(6c-18)+0.75(8c+32)=78 | | 3x+16=100 | | =x^3-4x^2-25x+100 | | 2c+6c=81 | | -14+3a=10a | | 4x-9=28x+9 | | 4m+3m=42 | | 3(2x-14)=6(x-2) | | 8-2s-3-s=-4+18 | | 17*5=x | | 29+15x=-x-3 | | 65=5-8x+2x | | 3x-8=4y+4 | | x-0.10=63 | | (2/3)n+8=0.5n+2 | | 2g+12=28 | | x^2-7x-294=0 | | -8(5t-4)+t=32 | | 4-6x=7-3x | | 14-3t+t-5=-4-1 | | -2(3y-6)+4(5y-8)=-18 | | 8-2x=24-8x | | 19x-7=7+12x |